Infection and chronic disease - Ewald, Paul (Henry Stewart Talks, 2007)
Chronic diseases (cystic fibrosis, atherosclerosis, tuberculosis), Risk factors, Primary and secondary causes, Categories of disease causation, Risk factors and disease causation, The e4 allele and the thrifty genotype hypothesis, Geographical variations in allele frequencies, Pathogen vulnerability hypothesis, Environmental causations (smoking, high fat diet, alcohol, garlic, iron), Drug treatment and atherosclerosis